PERLINDUNGAN HUKUM DAN KEKERASAN SEKSUAL TERHADAP PEREMPUAN DALAM HUKUM HINDU - Ni Wayan Sudarmini (Belom Bahadat, 2022)
Woman is a persons identity that is judged by gender. Women often get negative behavior from men, because of the inability to fight back. For example, getting an act of sexual violence committed by a patner or husband. Sexual violence ia an act carried out by a person by force in an attempt to have sexual intercourse. This action will cause suffering or harm to others, especially women. In Manawa Dharmasastra II. 56 it is clearly stated that “where women are respected, there the gods are happy, but where they are not respected, there is no sacred ceremony of any kind”. It means never hurt a women if you want happiness in her life. There are several concepts of Hindu teaching that can be applied to prevent acts of sexual violence. Among them are the teaching of chess purusa arta, where to get art and fulfill lust or kama be based on dharma. Then the teaching of tri kaya parisuda which means that every thought, word and deed must be good or holy. While the latter is the teaching of tat twam asi, where this teaching is interpreted as I am you and you are me. It is forbidden to hurt each other, because all humans and even all living things are brothers, vasu daiva kuthum bhakam.